Determinants of foreign direct investment in Central and Eastern Europe: panel data analysis results - Snježana Zarić (Anali Ekonomskog fakulteta u Subotici, 2022)
The diffusion of technology and the spillover of knowledge that accompanies foreign direct investment have made all countries, especially those in transition, interested in this type of capital inflow. Accordingly, in this paper, we have applied econometric panel models to identify determinants of foreign direct investment in Central and Eastern European countries. Our results indicate that differences in foreign direct investment flow in the analyzed countries can, to a large extent, be explained by traditional factors such as the availability of skilled labor force, labor costs, infrastructure quality, and market size. In addition, the quality of institutions, primarily democratic government, an independent judiciary, and the absence of corruption, also significantly influence foreign companies' decisions about where to invest in countries in the region.